(untitled) (Third Sector Social Economic Review, 2025)
The purpose of this study is to determine the awareness of medical documentation and secretarial department students about artificial intelligence applications used in education. For this purpose, the researcher asked questions such as ""What is the definition of artificial intelligence?"", “What artificial intelligence applications are used in education at universities?”, “What are the problems encountered in artificial intelligence applications used in education at universities?” and “What are your solution suggestions for the problems encountered in artificial intelligence applications used in education at universities?” He sought answers to his questions. This research is a qualitative study and was conducted using the phenomenological design. To collect data, the researcher used semi-structured interview technique. The data obtained with this method was analyzed from a descriptive perspective. The sample of the research consists of 10 students studying in the medical documentation and secretarial department of Amasya University. Accordingly, the students of the medical documentation and secretarial department who participated in the study defined the concept of artificial intelligence as software that makes life easier, virtual intelligence, thinking technology, installation, computing robot and smart assistant. Participants stated that the artificial intelligence applications used in education at universities are ChatGPT, Perplexity, and Chatbot. In addition, the participants expressed their opinions about the problems encountered in artificial intelligence applications used in education at universities as missing or excessive information, giving the answer in English, giving late answers, and giving the same answer to different problems. In this regard, the participants made suggestions that their opinions should be updated regarding the solutions to the problems encountered in artificial intelligence applications used in education at universities, the language issue should be corrected and the program should be accelerated.